2011
DOI: 10.1007/s10592-011-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic diversity in the critically endangered Central American river turtle: human influence since the Mayan age?

Abstract: We conducted a phylogeographic analysis of the strictly aquatic and critically endangered Central American river turtle, Dermatemys mawii, as part of a conservation management program for the species. We sampled 238 individuals from 15 different localities throughout the species range. Using sequence fragments from the mtDNA Cyt b and ND4 genes, we identified 16 different haplotypes. Overall, our results reveal a signal of phylogeographic structure throughout the range, which appears to have been secondarily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 61 publications
4
35
0
3
Order By: Relevance
“…We test to what extent the results from the nuclear genome show concordance with previously published mtDNA structuring [16]. Assessing and maintaining genetic diversity is pivotal for conservation management plans that aim to protect the evolutionary potential of the species.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…We test to what extent the results from the nuclear genome show concordance with previously published mtDNA structuring [16]. Assessing and maintaining genetic diversity is pivotal for conservation management plans that aim to protect the evolutionary potential of the species.…”
Section: Introductionmentioning
confidence: 74%
“…Recently, a study that characterized mtDNA variation in the species found signatures of phylogeographic structuring and phylogenetic splits among lineages up to a divergence of 2% [16]. A divergence of 2% at mtDNA loci in turtles can warrant species-level distinction [17].…”
Section: Introductionmentioning
confidence: 99%
“…During interviews with some fishermen, adult size was mentioned to be smaller in our study area, than those fishermen have seen in other States as Tabasco [16]. The genetic differences found in this population by Gonzalez-Porter et al [37], may be associated with adult size. This issue needs further investigation, and results may contribute to exercise conservation measures focus in this population due to its differentiation.…”
Section: Discussionmentioning
confidence: 41%
“…This suggests that despite its prolonged use as a source of food for centuries [37,38], this species has been understudied. Notwithstanding the geographic proximity of the studies done in Belize up to date and as a result of the present work [16], Rio Hondo has started to be considered as a priority site for the conservation of the species [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation